Attitudes of Managers Towards Implementing the Concept of Intellectual Capital: Case Study Brega Oil Marketing Company Working in Benghazi City - محمد , حسين (Dirasat in Economics and Business, 2020)
This research aims at identifying attitudes of managers towards implementing of the concept of intellectual capital dimensions of (human capital, capital structural, capital relations) in Brega Oil Marketing Company in the city of Benghazi. The research consists of all managers of senior and middle management in Brega Oil Marketing Company in Benghazi, The research uses the method of comprehencive survey of members of the research population, as their number reached (88) staff, distributed to form the questionnnaire as the main instrument of the research, and retrieval (74) form of replacement convertible statistical analysis. The research concluded a set of results, including: That the level of awareness of members of society of the research of the concept of intellectual capital came to the level of high, The attitudes out that the direction of the members of the research population towards the concept of intellectual capital came to the level of high. The research recommended an increase to deepen the awareness of managers to the concept of intelectual capital, as well as the attention of human resources as one of the most important sources of intellectual capital for the company under this research.